Analisis Haditst-Hadits Tentang Pedoman Hidup Dalam Dasar Penyelenggaraan Pendidikan - Nadya Elpita Sari; Ratna Sari; Rivaldi Rivaldi; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
Hadits is a guideline for Islamic law after the Koran. Hadith have a role in clarifying and strengthening every problem experienced by Muslims, so that they can live their lives in accordance with the guidance of the Prophet Muhammad and make it a foundation in Islamic education. Islamic education does not only emphasize human spiritual aspects, but also emphasizes human life comprehensively. The purpose of this article is to examine hadith related to life guidelines in the provision of education. This research is a type of library study research with qualitative methods. The analysis findings show that hadith are really needed as a basis for life to explain every problem faced and strengthen every law contained in the Koran. Furthermore, the hadith also serves as a guide for the lives of Muslims so that they can live their lives with benefit.